IDENTIFICATION OF MARINE DEBRIS IN THE BEACH OF KODINGARENG LOMPO ISLAND, MAKASSAR CITY - Werorilangi, Shinta; Angelica, Pricilia Gaby; Lanuru, Mahatma; Rasyid , Abdul (Hasanuddin University, 2022)
Marine debris may become a serious threat because of the increasing in its quantity every day, especially in marine areas around the world. The purpose of this study was to identify the amount, weight, and type of marine debris and to determine the abundance based on the amount and weight present in the coastal area on Kodingareng Lompo Island, Makassar City. This research was carried out during the ebb of the east monsoon period, i.e., in June 2021. The most common types of waste found in the three observation locations were plastic waste. The abundance of waste based on the amount is most commonly found at station 2, which is located near a residential area, so that most of the waste at the station is household waste. Meanwhile, the greatest abundance of weight was also observed at station 3 which has the widest intertidal area and the majority of the waste there came from a type of cloth which was larger than other wastes. Station 3 also has a faster flow rate than the other stations. The existing waste facilities on Kodingareng Lompo Island in the form of garbage motorbikes and Garbage Banks in general have not been effective. Several factors that can also worsen, i.e., lack of understanding, low awareness, and laziness of the community in managing their waste, people prefer to throw garbage into the sea, so the accumulation of marine waste in the coastal area of Kodingareng Lompo Island may have a negative impact in various fields of life.